Post-migration treatment targets associated with reductions in depression and PTSD among survivors of torture seeking asylum in the USA. (January 2019) - Kashyap, Shraddha; Page, Andrew C.; Joscelyne, Amy
Highlights: Torture survivors face both pre and post-migration stressors. Emerging research highlights the impact of post-migration stressors on wellbeing. Relieving post-migration stress despite trauma, can improve wellbeing. Housing, employment and lower chronic pain were associated with better wellbeing. These were significant after accounting for pre-migration trauma and visa status. Abstract: Mental health research among asylum seekers and refugees has largely focused on effects of pre-migration trauma on post-migration wellbeing. While emerging literature highlights the importance of post-migration factors, we do not yet understand how addressing these factors may influence change in psychological distress. This study uses archival clinical data to identify post-migration correlates of reductions in distress among torture survivors, after accounting for pre-migration trauma. Depression (Patient Health Questionnaire-9) and Post Traumatic Stress Disorder (PTSD; Harvard Trauma Questionnaire) were measured among torture survivors following 6 months of interdisciplinary treatment (N = 323). Relationships between pre-, post-migration factors, and changes in symptom levels from intake to six months follow-up, were evaluated using regression analyses. Average levels of depression and PTSD significantly reduced after six months of treatment. Higher exposure to pre-migration trauma, female gender, and change to a more secure visa status were associated with reduced distress. Accessing more social services and not reporting chronic pain were associated with reduced PTSD. Stable housing and employment significantly moderated the relationship between lower chronic pain and reduced PTSD. Although effect sizes were small, results emphasize the importance of post-migration factors on wellbeing among torture survivors and are a first step towards identifying key treatment targets.